PENGARUH JENIS AIR PERENDAM TERHADAP KANDUNGAN VITAMIN C, SERAT, DAN PROTEIN TEPUNG MANGGA (Mangifera Indica L.) (Universitas Negeri Semarang, 2013)
Mango is a tropical and sub-tropical fruit known throughout the world because it tastes good and fresh. However the freshness of mangoes can not stand for too long so it is necessary to have a good post-harvest handling and management. Mango processing will increase the economic value of agricultural production. One of the method to maintain function and quality in the mango processing, mango can be processed into other form such as mango flour. In the processing of mango powder still can be found the low level of nutrients such as vitamin C, fiber and protein, which caused by the occuring of change in raw material during the drying process. To prevent such change, an arrangement of a soaking method should be made. This study aims to determine the effect of water on the process of making mango powder on the content of vitamin C, fiber and protein. From the research results, it can be concluded that the relatively good conditions for the process of making mango powders done by using cold water (0 oC) as a soaking water. Soaking water influenced the content of vitamin C, fiber and protein.